Mecanismo de redução de energia assegurada e o seu impacto no planejamento e organização da engenharia de manutenção da geração - Antonio Carlos Arantes (2010)
The current master thesis was developed with the objective of studying theresolution guidelines 688/2003 which regulates the application of InsuredEnergy Reduction Mechanism - MRA as the mechanism used by the BrazilianElectricity Regulatory Agency to encourage the availability of generationfacilities members of National Interconnected System.This work intends to evaluate the impact of MRA in the planning andorganization of the Maintenance Engineering of Generation and to proposeprocedure for betterment of system maintenance relatives the MRA. The textcontains explanatory notes on the main commands of the standard andpractical examples of calculating the Insured Energy Reduction Mechanism tothe main functions of generation. At the end, is proposed a study together withthe concessionaire of generation for evaluation of the results for thisconcessionaire and the electrical system after the obtainment of unavailabilityinitiated by the National Electric System Operator - ONS, when there will be asufficient data number for analysis.